Radiation-induced graft polymerization of elastin onto polyvinylpyrrolidone as a possible wound dressing - Del Prado-Audelo, María Luisa; Gómez-Zaldivar, Francisco J.; Pérez-Díaz, Mario; Sánchez-Sánchez, Roberto; González-Torres, Maykel; González-Del Carmen, Manuel; Figueroa-González, Gabriela; Sharifi-Rad, Javad; Reyes-Hernández, Octavio D.; Cortés, Hernán; Leyva-Gómez, Gerardo (Cellular and Molecular Biology, 2021)
The purpose of our study was to obtain new wound dressings in the form of hydrogels that promote wound healing taking advantage of the broad activities of elastin (ELT) in physiological processes. The hydrogel of ELT and polyvinylpyrrolidone (PVP; ELT–PVP) was obtained by cross-linking induced by gamma irradiation at a dose of 25 kGy. The physicochemical changes attributed to cross-linking were analyzed through scanning electron microscopy (SEM), infrared spectroscopy analysis with Fourier transform (FTIR), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA). Furthermore, we performed a rheological study to determine the possible changes in the fluidic macroscopic properties produced by the cross-linking method. Finally, we accomplished viability and proliferation analyses of human dermal fibroblasts in the presence of the hydrogel to evaluate its biological characteristics. The hydrogel exhibited a porous morphology, showing interconnected porous with an average pore size of 16 ± 8.42 µm. The analysis of FTIR, DSC, and TGA revealed changes in the chemical structure of the ELT–PVP hydrogel after the irradiation process. Also, the hydrogel exhibited a rheological behavior of a pseudoplastic and thixotropic fluid. The hydrogel was biocompatible, demonstrating high cell viability, whereas ELT presented low biocompatibility at high concentrations. In summary, the hydrogel obtained by gamma irradiation revealed the appropriate morphology to be applied as a wound dressing. Interestingly, the hydrogel exhibited a higher percentage of cell viability compared with ELT, suggesting that the cross-linking of ELT with PVP is a suitable strategy for biological applications of ELT without generating cellular damage.